Toward Sustainable Regions Essays in Honor of Kiyoko Hagihara - Asahi, Chisato; Horie, Noriko (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book deals with regional sustainability, which is one of the biggest issues in Japan today, and presents suggested methods and cases to show how regional management should be carried out. Today, regions in Japan are facing long-term global challenges such as changes in climate and in international relations, as well as regional financial difficulties due to depopulation and aging. Additional causes are the decline of traditional culture and community sustainability, the crisis of public services, inner- and inter-regional disparities, disaster response, and other local and region-specific issues that are intricately related. To meet the challenge of those issues, local actors must deal with the regional issues themselves and solve them in cooperation with various other stakeholders. From this perspective, the book exhibits regional management frameworks, focusing especially on evaluation, decision making, and aid in multi-dimensional approaches, and examines case studies for making regions sustainable by allowing diverse actors to realize diverse values and standards in cooperation. The chapters cover a wide range of disciplines, including urban science, economics, geography, landscape, real estate, and public finance, which makes it possible to shed light on a particular region. This book comprises a collection of essays celebrating the life and work of Kiyoko Hagihara, honorary professor of the Graduate School of Urban Science, Tokyo Metropolitan University, Japan. Essay contributors include her former students as well as regional scientists with similar interests.
Chapter 1 Greening in Vacant Lots and Regional Community in Urban Area -- Chapter 2 Challenges of a Large Park that can be Seen in the Wake of the COVID-19 Pandemic Case of Hitachi Seaside Park -- Chapter 3 Supporting Organisations for Social Enterprises: Focus on Fundraising -- Chapter 4 Changes in the Electricity Market and the Emergence of Regional Energy Business in Japan: Toward the Realization of a Comprehensive Supply Scheme for Local Public Services -- Chapter 5 The institutional design of a comprehensive supply scheme for sustainable local public services - Theoretical considerations and case study of Stadtwerke -- Chapter 6 Evaluation of the Educational Role of Urban Facilities and Their Contribution to Regional Sustainability -- Chapter 7 A Study on the Economic Evaluation of Public Facilities Regional Utilisation Other than Intended Purposes of School Facilities -- Chapter 8 Land Value Differences Based on Approach Methodologies: Analysis using Land Market Value Publications in Tokyo -- Chapter 9 An overview of Indicator-based Approach of Flood Vulnerability Assessment -- Chapter 10 A Study of Evacuation and Life Rebuilding after a Flood Disaster -- Chapter 11 Consideration on the subject and criteria of the minutes of the environmental assessment deliberation meeting by exploratory text analysis.
Keywords: Regional economics; Spatial economics; Facility management; Urban economics; Nonprofit organizations; Regional and Spatial Economics; Facility Management; Urban Economics; Non-Profit Organizations and Public Enterprises